Reka Bentuk Pembelajaran Bahasa Arabberasaskan Laman Sesawang - Khalik, Muh. Fihris (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2018)
The aims of the research were to develop and evaluate a website of Arabic teaching forSenior High School (SMA) that offers interactive, effective and innovative learning environment. The research methodology involved two phases: (i) development of Arabic website and (ii) evaluation of website from the aspects of pedagogical approaches and multimedia elements. In the development phase the researcher used analysis, design, development, implementation, evaluation (ADDIE) model. And inthe evaluation phases the researcher used formative, summative and the pre and thepost test assessment. The effectiveness test was conducted to determine the Arabic achievement of students who used website compared to students who used conventional methods. The research findings revealed that website has successfully created interactive, effective and innovative learning environment. It was also revealed that students who used website had performed better than students who used conventional methods in learning Arabic. This research had successfully contributedto the following: (i) the design of the development methodology of the Arabic website; BEBAS (ii) the design of the instructional design model of website; (iii) the prototype of the Arabic website; BEBAS (iv) the developments of the following modules:Tutorials, Exercises, Download, Communication, and Links; and (v) the findings ofthe usability test conducted on the Arabic website. The website could be considered asan alternative teaching and learning virtual tool in exploring the skill of Arabic.